1998
DOI: 10.1007/s004360050434
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to nonrepeat sequences of antigen Pf155/RESA of Plasmodium falciparum inhibit parasite growth in vitro

Abstract: Immune responses to the repeat regions of the Plasmodium falciparum antigen Pf155/RESA have been extensively studied, and antibodies to the repeats are known to interfere with parasite growth both in vitro and in vivo. Less is known with regard to the effect on parasites of antibodies to the nonrepeat regions of the antigen. In the present study, rabbits were immunized with synthetic peptides corresponding to three different nonrepeated sequences of antigen Pf155/RESA. The reactivity of the antibodies with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
0
13
1
Order By: Relevance
“…In the present study we show that af®nity-puri®ed human antibodies reactive with Pf155/RESA non-repeat sequences as presented in MAP14 and 15 also have the capacity to inhibit parasite growth in vitro. In contrast to most antibodies to Pf155/RESA repeat sequences [44], the rabbit antibodies to non-repeat sequences of the antigen were shown also to inhibit the in vitro growth of parasites de®cient in Pf155/RESA [18], indicating cross-reactivity with some other antigen. Whether the corresponding human antibodies show a similar inhibitory effect on Pf155/RESA-de®cient parasites remains to be tested.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…In the present study we show that af®nity-puri®ed human antibodies reactive with Pf155/RESA non-repeat sequences as presented in MAP14 and 15 also have the capacity to inhibit parasite growth in vitro. In contrast to most antibodies to Pf155/RESA repeat sequences [44], the rabbit antibodies to non-repeat sequences of the antigen were shown also to inhibit the in vitro growth of parasites de®cient in Pf155/RESA [18], indicating cross-reactivity with some other antigen. Whether the corresponding human antibodies show a similar inhibitory effect on Pf155/RESA-de®cient parasites remains to be tested.…”
Section: Discussionmentioning
confidence: 72%
“…We have recently also shown that rabbit antibodies to non-repeat sequences in the N-terminal part of Pf155/RESA, including antibodies to MAP14 and 15, inhibit parasite growth in vitro [18,43]. However, antibodies to the cytoadherence related motifs in Pf155/RESA as presented in MAP16 and 18 were without effect in this respect [43].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations